2015
DOI: 10.2460/ajvr.76.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Regional metabolite concentrations in the brain of healthy dogs measured by use of short echo time, single voxel proton magnetic resonance spectroscopy at 3.0 Tesla

Abstract: Metabolite concentrations differed among brain parenchymal regions in healthy dogs. This study may provide reference values for clinical and research studies involving (1)H MRS performed at 3.0 T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 51 publications
2
31
0
Order By: Relevance
“…With regard to specific metabolite findings for the lobes interrogated, the differences detected between the thalamus and the parietal lobe for N‐ acetyl aspartase/choline were similar to the results of prior studies in people and dogs . A previous canine study reported differences in N‐ acetyl aspartase, choline, creatine, and myo ‐inositol for the following regions: basal ganglia, thalamus, parietal lobe, occipital lobe, and cerebellum . We found a difference between the parietal lobe and the thalamus, which is similar to a prior study in dogs .…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…With regard to specific metabolite findings for the lobes interrogated, the differences detected between the thalamus and the parietal lobe for N‐ acetyl aspartase/choline were similar to the results of prior studies in people and dogs . A previous canine study reported differences in N‐ acetyl aspartase, choline, creatine, and myo ‐inositol for the following regions: basal ganglia, thalamus, parietal lobe, occipital lobe, and cerebellum . We found a difference between the parietal lobe and the thalamus, which is similar to a prior study in dogs .…”
Section: Discussionsupporting
confidence: 90%
“…Spectroscopy was successfully performed in six of eight dogs (Figure ). Spectra were deemed normal based on historically available comparisons in the available canine literature . Single‐voxel spectroscopy was performed with a mean acquisition time of 6.4 ± 0.26 min.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations